Purification and Characterization β - lactamase produce from local isolate Klebsiella pneumonia - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
Beta-lactamase was purified from local isolate Klebsiella pneumonia by several steps included precipitation with ammonium sulphate at 20-40% saturation, DEAE- ion exchange chromatography and gel filtration on Sephacryl S-200 column. The obtained purification fold and recovery were 32.66; 47.04% respectively. The characterization of the purified beta-lactamase showed that the molecular weight was about 4000 daltons as determined by gel filtration.Purified enzyme had an optimal pH of 7 for activity and an optimal stability between pH 6.5-7.5, results shows that the optimal temperature appear to be 35 ? C .During storage the enzyme retained 72% at -20 ? C and retained 25% of the activity at the same period at 4 ? C.